2015
DOI: 10.1108/ijpdlm-10-2013-0258
|View full text |Cite
|
Sign up to set email alerts
|

Market adoption of reverse factoring

Abstract: Purpose – The purpose of this paper is to show that market dynamics can significantly influence the lifecycle and value of a supply chain finance (SCF) arrangement. Design/methodology/approach – Based on a review of scientific and trade literature, the authors construct a model of market dynamics for reverse factoring, a specific type of SCF arrangement. The authors assume that firms’ participation in a reverse factoring arrangement is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 24 publications
2
50
0
5
Order By: Relevance
“…One possible way to solve models under further assumptions would be using simulation approaches such as those used by Dello Iacono et al (2015); however, such analyses are beyond the scope of our paper.…”
Section: Resultsmentioning
confidence: 99%
“…One possible way to solve models under further assumptions would be using simulation approaches such as those used by Dello Iacono et al (2015); however, such analyses are beyond the scope of our paper.…”
Section: Resultsmentioning
confidence: 99%
“…Suppliers have tended to benefit as well, through better access to financing and/or through reductions in their own financing costs (Liebl, Hartmann, & Feisel, 2016; van der Vliet, Reindorp, & Fransoo, 2015). Supporting the rising interest in SCF among executives, academic research has shown how SCF can benefit all parties involved: buyers, suppliers, and SCF providers (Chen & Gupta, 2014;Dello Iacono, Reindorp, & Dellaert, 2015;Grueter & Wuttke, 2017;Tanrisever, Cetinay, Reindorp, & Fransoo, 2012;van der Vliet et al, 2015;Wuttke, Blome, Heese, & Protopappa-Sieke, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of its quantitative contributions for benefits assessment, Tanrisever et al (2015) and Van der Vliet et al (2015) focus their analysis on the duality between the discount and extension of payment terms, a factor qualitatively confirmed by the analysis of Liebl et al (2016). Dello Iacono et al (2015) analyse the adoption process of RF by a large buyer and the subsequent onboarding of suppliers. This article builds on its assessment of tangible benefits and further extends it to include the aforementioned duality between the discount and extension of payment terms.…”
Section: Literature Reviewmentioning
confidence: 99%